The impact of slope engineering as a green technology towards the environment - Hassan, Nur 'Adilah; Ab Sani, Jasasikin (2016)
Human intervention on the environment affects the change of landforms all over the world. As the population keeps on growing, more land will be required for different uses and activities, whether it is for lodging, cultivating or industrial uses. Another human activity that influences slope destruction is the construction of buildings.However, in demanding area of land for the necessities of human, land is regularly being manhandled and changed drastically due to overuse. The massive alteration on the slope area has caused the soil erosion issues. The current research has shown that the biotechnical erosion or bioengineering technique is the green approach to prevent the soil erosion .This paper presents the application of bioengineering techniques on slope engineering that would give positive impact towards the environment. The data for this study was collected using primary and secondary data by doing site survey and observation on checklists that extracted from the literature review.The finding of the study inspired to find the best technique in mitigating the issues of soil erosion by the application of bioengineering techniques on slope engineering. In conclusion, the bioengineering techniques are regarded as green technology that would give positive impact as it can increase the safety factors on the slopes as well as act as soil erosion control.